Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Efficient strategy for the construction of both enantiomers of the octahydropyrroloquinolinone ring system: total synthesis of (+)-aspidospermidine - Pandey, Ganesh; Burugu, Shiva Kumar; Singh, Pushpendra (Organic Letters, 2016)
An efficient and highly stereoselective intramolecular [3 + 2] cycloaddition of nonstabilized azomethine ylide generated from a designed bicyclic aminal precursor is reported for the synthesis of both (-)- and (+)-octahy-dropyrroloquinolinone. One of the enantiomers is further advanced to accomplish the total synthesis of (+)-aspidospermidine.